2011
DOI: 10.4314/sjms.v6i1.67273
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Retinopathy, Nephropathy and Peripheral Neuropathy among Adult Sudanese Diabetic Patients

Abstract: Diabetes Mellitus is a worldwide common metabolic disorder. Increasing prevalence of diabetes, lack of proper education about the nature and course of the disease and necessary control are the main factors for an early onset of micro vascular complications. Objective: To correlate between retinopathy, nephropathy and neuropathy, among adult Sudanese diabetic patients at Elshaab Teaching hospital, Ahmed Gasim Teaching hospital and Gabber Abu Eleaz centre, from December 2006 to September 2008. Methodology: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Moderate and severe proliferative diabetic retinopathy were seen in higher grades of chronic renal failure. Our results are in comparison with this study [32]. DR is invariably present in cases of diabetic nephropathy and more severe forms of retinopathy are observed with progression of renal disease.…”
Section: Discussionsupporting
confidence: 82%
“…Moderate and severe proliferative diabetic retinopathy were seen in higher grades of chronic renal failure. Our results are in comparison with this study [32]. DR is invariably present in cases of diabetic nephropathy and more severe forms of retinopathy are observed with progression of renal disease.…”
Section: Discussionsupporting
confidence: 82%
“…Totally, 1,278 studies were retrieved, of which, 1,261 studies were found from six international databases and the remaining 17 were through manual search. Databases includes; PubMed 161 [44,45], 2 research paper from Egypt [46,47],the remaining was from Ghana [15],Uganda [48],and Tanzania [49]. The highest prevalence of diabetic peripheral neuropathy (83.4%) and the lowest (7.5%) were reported from Nigeria.…”
Section: Search Resultsmentioning
confidence: 99%
“…A total of 23 studies with 269,691 participants were included in this meta-analysis. Overall information regarding the prevalence was obtained from various areas across Africa: 10 studies from Nigeria [14, 18-20, 22, 36-40], 4 article from Ethiopia[16, 24, 41, 42], 2 studies from Cameroon[23, 43], 2 article from Sudan[44, 45], 2 research paper from Egypt[46, 47],the remaining was from Ghana [15],Uganda [48],and Tanzania [49]. The highest prevalence of diabetic peripheral neuropathy (83.4%) and the lowest (7.5%) were reported from Nigeria.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 23 studies with 269,691 study participants were included in this meta-analysis. Overall information regarding the prevalence of DPN in DM patients was obtained from various countries across Africa including 10 studies from Nigeria [14, 18-20, 22, 37-41], four from Ethiopia [16,24,42,43], two from Cameroon [23,44], two from Sudan [45,46], two from Egypt [47,48], and one each from Ghana [15], Uganda [49], and Tanzania [50]. The highest and lowest prevalence of DPN was 83.4% [22] and 7.5% [41] respectively, which were reported from Nigeria.…”
Section: Baseline Characteristics Of the Included Studiesmentioning
confidence: 99%